Industrial forecasting : a review of statistical techniques and the development of a computer-based forecasting system for a small industry - Potgieter, G.(Gerhard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1972.